CEO ACCOUNTING EXPERTISE: ITS IMPACT ON FINANCIAL STATEMENT QUALITY IN INDONESIAN PUBLIC FIRMS - Sumarta, Nurmadi Harsa; Amidjaya, Prihatnolo Gandhi (TEMA, 2023)
Following the growing access to firms' financial reports, we investigate the role of CEO accounting expertise on financial report quality in Indonesian listed firms. We analyze secondary data from 92 Indonesian listed firms in all industry sectors using multiple linear regression analysis. Our findings demonstrate that CEO accounting expertise positively affects financial report quality, by having more reliable financial information, better audit opinion, and on-time financial report submission. Our study provides implications to Indonesian firms to provide accounting knowledge to the CEO so that it would help build better accounting policies and practices to produce high-quality financial statements. This is very important as financial report quality increasingly provides positive implications to firms to achieve better accountability and market performance.